Age distribution of psoriasis clinical types: A single center study - Hasan Alakbarov; İlgen Ertam; Ayda Acar; Bengü Gerçeker Türk; İdil Ünal (Galenos Publishing House, 2021)
Background and Design: Psoriasis is a multifactorial, chronic inflammatory skin disease. Clinical and epidemiological parameters in psoriasis may vary in different age groups. The age of the patient is significant in the choice of treatment. We therefore aimed at performing a general and comparative assessment of epidemiologic and clinical parameters of patients with psoriasis according to four age groups. Materials and Methods: We assessed the files of patients with psoriasis who applied to our clinic between 2006 and 2016. Sex, age, duration of disease, family history of psoriasis, clinical types, psoriasis area and severity index, nail and joint involvement, associated comorbidities and dermatoses, and treatments for psoriasis were obtained from the patient files. They were then evaluated comparatively in four age groups: 0-18 years, 19-40 years, 41-65 years and over 65 years. Results: We enrolled 374 patients (54.3% male, 45.7% female). Age of the patients were between 6 years and 85 years (mean: 42.17±18.54 years), with 16% of the patients between the age of 0-18, 26.7% between 19-40, 45.5% between 41-65 and 11.8% above 65. Guttate psoriasis and generalized pustular psoriasis were observed more frequently in females (p=0.001). Plaque psoriasis was the most observed clinical type in all age groups, while between the age of 0-18 years, the frequency of guttate psoriasis (31,7%) increased significant compared to that in other age groups (p<0.001). Nail involvement in 41-65 years occurred in 64.7% of patients, while it was 18.3% in the 0-18 age group (p<0.001). Frequency of joint involvement was identified in 1.7% of the 0-18 age group, 4% of 19-40 age group, 8.8% of 41-65 age group and 9.1% of the age group above 65 years (p<0.001). Frequency of comorbidities significantly increased with increase in age (p<0.001). Conclusion: In this study, age was noted as a significant factor in distribution of clinical types, nail and joint involvement, comorbidities and selection of treatment modalities.